Translating the narrative of tolerance in designing a museum environment - Yaufik, Anggelia; Kusuma, Adriyan (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
The study explores the design of a museum environment based on the narrative of 'tolerance.' Museums deliver in-depth and interactive messages through creating spatial experiences that provides information and engages visitor's emotions. This academic design study utilises the narrative architecture approach to compose and create holistic spatial flow that guide visitors through various sensory experiences. The design of the museum environment consists of five core spaces with different flows of sensorial narrative related to the experience of tolerance, named Susila, Sahayanda, Sabah, Sadrah, and Segianya. The sequence between spaces allows for a coherent and progressive narrative of tolerance, enabling visitors to feel a deep involvement from one space to another. Sensorially, manipulation and organisation of spatial scales bring different experiences of light, texture, sound, and visuals to create a comprehensive and memorable experience. The application of narrative architecture allows the museum environment to evolve, not only as a place to exhibit artefacts but also as a dynamic educational platform. It provides important information about the history of tolerance-related events and reflectively enriches how the visitors experience the space. Connections between the conveyed narrative of tolerance and the space create a vibrant experience of the overall museum environment.